Pengaruh Stres Kerja, Gaya Kepemimpinan, Motivasi, Dan Budaya Organisasi Terhadap Kinerja Karyawan (Studi Kasus Pada Perawat Rumah Sakit Islam Unisma Malang) - Ridho Mukhlis Aristo; Muhammad Mansur; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study was to determine the effect of work stress, leadership style, motivation, and organizational culture on employee performance. The data collection method in this study used a questionnaire with a total sample of 64 nurses. The data analysis method used in this study is multiple linear regression analysis, based on the results of this study that work stress does not affect employee performance, leadership style affects employee performance, motivation does not affect employee performance and organizational culture affects employee performance.. Keywords : Work Stress, Leadership Style, Motivation, Organizational Culture,                    And  Employee Performance